Effectiveness of Black Cumin (Nigella sativa L.) Extract on Increasing Stamina in Male Mice (Mus musculus) - Melita, Raina Aulia; Maretha, Delima Engga; Nurokhman, Amin (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
AbstractResearch using ethanol extract from black cumin seeds aims to find out whether black cumin seed extract (Nigella sativa) can be effective in increasing the stamina of male mice. The research design used was a completely randomized design (RAL). The samples used were 24 male mice consisting of four treatments and six repetitions. The dosing treatment consisted of a normal control group (P0), 30 mg/kg weight (P1), 60 mg/kg weight (P2), and 120 mg/kg weight (P3). The swimming test method was used to determine the effect of increasing stamina on mice. Data on the swimming duration of mice were analyzed using the ANOVA test then continued using the Post Hoc Test, namely LSD. The average stamina of mice based on swimming duration was the highest, namely at a dose of 120 mg/kgW (P3). Administration of black cumin seed extract (Nigella sativa) at doses of 30 mg/kgBW, 60 mg/kgW, and 120 mg/kgW for 14 days provided effectiveness in increasing stamina in male white mice (Mus musculus) as indicated by an increase in the swimming duration of the mice in each treatment.AbstrakPenelitian menggunakan ekstrak etanol biji jinten hitam bertujuan untuk mengetahui apakah ekstrak biji jinten hitam (Nigella sativa) dapat berpengaruh terhadap peningkatan stamina mencit jantan. Rancangan penelitian yang digunakan ialah rancangan acak lengkap (RAL). Sampel yang digunakan sebanyak 24 ekor mencit jantan yang terdiri dari empat perlakuan dan enam pengulangan. Perlakuan pemberian dosis terdiri atas kelompok kontrol normal (P0), 30 mg/kgBB (P1), 60 mg/kgBB (P2), dan 120 mg/kgBB (P3). Metode swimming test digunakan untuk mengetahui efek peningkatan stamina terhadap mencit. Data durasi renang mencit dianalisis menggunakan uji ANOVA kemudian dilanjutkan menggunakan uji Post Hoc Test yaitu LSD. Rata-rata stamina mencit berdasarkan durasi renang yang paling tinggi yaitu pada dosis 120 mg/kgBB (P3). Pemberian ekstrak biji jinten hitam (Nigella sativa) pada dosis 30 mg/kgBB, 60 mg/kgBB, dan 120 mg/kgBB selama 14 hari dapat berpengaruh dalam peningkatan stamina pada mencit putih jantan (Mus musculus) ditandai meningkatnya durasi renang mencit dimasing-masing perlakuan.